Researching organizations the practice of organizational fieldwork - Jones, Matthew (Los Angeles SAGE, 2014)
Although there are plenty of books that discuss the principles, the philosophy and the techniques of research in organisations, it is much harder to find information on what doing research in organisations actually involves in practice. Yet this is often one of the most challenging, but also most interesting, aspects of a study. Drawing on examples and debates from a broad range of disciplines (such as criminology, education and social anthropology as well management) Researching Organisations explores the issues that researchers may encounter when carrying out fieldwork in organisations. From getting in to an organisation at the start of the research to getting out and maybe back again at the end, the book offers systematic guidance to help researchers navigate the messy reality of fieldwork. Researching Organisations is designed for graduate level researchers who may be undertaking fieldwork for the first time, but also for those who wish to gain an understanding of research practice.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Organization -- Research -- Methodology